Implementasi Home Visit dalam Upaya Meningkatkan Pembelajaran PAI di SDIT al-Azhar Kediri - Amalia, Husna (Didaktika Religia, 2016)
The study describes the implementation of home visit to develop Islamic teaching at SDIT al-Azhar Kediri. This is qualitative research. The findings are as follows. Firstly, the implementation of home visit at SDIT al-Azhar Kediri consists of planning, organizing, actuating, and evaluating. Secondly, the results of home visit at SDIT al-Azhar Kediri are to develop Islamic teaching in in the form of knowledge, religiousity, and attitude. Thirdly, the obstacles of the implementation of home visit can be seen from the quality of time, the location of house, and the capacity of teacher.